2016
DOI: 10.1159/000446564
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive Hemicraniectomy in Malignant Middle Cerebral Artery Infarction: The ‘Real World' Beyond Studies

Abstract: Background: Decompressive hemicraniectomy (DHC) is life-saving in patients with malignant middle cerebral artery infarction (MMI), but outcome, perspectives and complications after DHC in daily practice are largely unknown. Methods: From 2008 until 2014, we extracted patient's characteristics as well as complications from our database for patients with MMI who underwent DHC. Additionally, we analysed medical records from the different rehabilitation steps. Results: We identified 48 consecutive patients (mean 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Only 3 studies reported anatomic stroke subtypes 18,30,31. Only 4 reported stroke severity 18,22,32,33. These 4 used the National Institutes of Health Stroke Scale (NIHSS), with scores ranging from 9 to 19 and mean NIHSS scores reported as 9,22 11,18 14,32 and 19 33…”
Section: Resultsmentioning
confidence: 99%
“…Only 3 studies reported anatomic stroke subtypes 18,30,31. Only 4 reported stroke severity 18,22,32,33. These 4 used the National Institutes of Health Stroke Scale (NIHSS), with scores ranging from 9 to 19 and mean NIHSS scores reported as 9,22 11,18 14,32 and 19 33…”
Section: Resultsmentioning
confidence: 99%
“…A total of 4290 studies were screened on the title/abstract. Eventually, 47 studies were assessed full text, of which 27 excluded: delirium diagnosis not reproducible (n s (number of studies) = 9), [20][21][22][23][24][25][26][27][28] full text not found (n s = 3), [29][30][31] duplicate (n s = 3), [18,32] paediatric patients (n s = 1) [33], overlapping populations (n s = 3), [4,34,35] no delirium assessment (n s = 1), [36] no original data (n s = 2) [37,38] and an unclear number of patients undergoing intracranial surgery (n s = 5) [39][40][41][42][43]. Finally, 20 paper were included in the qualitative analysis and 18 papers in the quantitative analysis (n p (number of patients) = 5083).…”
Section: Systematic Searchmentioning
confidence: 99%
“…However, in a real-world setting, patients who undergo hemicraniectomy present frequently with complications that were underestimated in randomized clinical trials and may worsen the functional outcome, with 80% of survivors completely dependent (mRS 4-5). 20 Recently, new guidelines on CED management in neurocritical care patients have been published. 21 For acute treatment, they suggest using either hypertonic sodium solutions or mannitol for the initial management of CED in patients with acute ischemic stroke (conditional recommendation, low-quality evidence), although neurological outcomes appear to be not affected.…”
Section: Discussionmentioning
confidence: 99%
“…There is continued uncertainty about the benefit and risks of surgical decompression in patients with space-occupying hemispheric infarction if performed after the first 48hours. However, in a real-world setting, patients who undergo hemicraniectomy present frequently with complications that were underestimated in randomized clinical trials and may worsen the functional outcome, with 80% of survivors completely dependent (mRS 4–5) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%